PENINGKATAN KETERAMPILAN BERBAHASA INDONESIA DENGAN SIMULASI TES UKBI SEBAGAI TES STANDAR BAHASA INDONESIA - Syihaabul Hudaa (Salingka, 2019)
Indonesian people in the correct language practice often find language barriers, one of them is the application of Indonesian language rules. In fact, in appreciating the Indonesian language, the general public is not aware of a standard test that measures language skills, namely UKBI. The purpose of writing this article is to convey that the UKBI simulation test can be used in an effort to measure ability and improve the language skills of the general public. The method used in this study is direct action by providing training. Value retrieval is carried out in two cycles, so that the differences can be seen before training. The author found a significant increase in the Semanan community's language skills. Cycle I shows the existence of a community that has a predicate: limited to 7%, marginal 7%, average 23%, middle 36%, and superior 27%. Conversely, cycle II shows an increase in predicate, namely: 17%, middle 47%, superior 33%, and very superior 3%. It can be seen that the results of the second cycle have no more people with a limited predicate.